Perl in a nutshell : a desktop quick reference - Patwardhan, Nathan; Siever, Ellen; Spainhour, Stephen; O'Reilly & Associates (Beijing : O'Reilly, 2004)
Presents six Perl texts in HTML format.
System requirements: Browser software (such as Netscape Communicator , Internet Explorer, or Lynx) supporting HTML 4.0 or earlier versions; Java-enabled browsers supporting Java version 1.1.2 or later; CD-ROM dr ive.
Keywords: Perl (Computer program language)